The diversity of smallholder wool production and its marketing aspects : a case study at Xume, Eastern Cape, South Africa - Perret, S. (Sylvain) (University of Pretoria, 2013)
Dissertation (MInstAgrar (Agricultural Economics))--University of Pretoria, 2008.